2022
DOI: 10.1155/2022/4607735
|View full text |Cite|
|
Sign up to set email alerts
|

The Clinical Study of Bladder Flap Ureteroplasty (Psoas Hitch) in the Treatment of Lower Ureteral Injuries and Strictures (19 Cases)

Abstract: Objective. The aim of this study was to investigate the efficacy and safety of bladder flap ureteroplasty (psoas hitch) in the treatment of lower ureteral injuries and strictures. Methods. 19 patients with lower ureteral injuries and strictures scheduled for a bladder flap ureteroplasty (psoas hitch) in our hospital from January 2020 to January 2021 were recruited. The outcome measures included treatment efficacy and safety. Results. The operative time, intraoperative bleeding, catheter extubation time, hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%